Synthesis of a New Phenyl Chlormethine-Quinazoline Derivative, a Potential Anti-Cancer Agent, Induced Apoptosis in Hepatocellular Carcinoma Through Mediating Sirt1/Caspase 3 Signaling Pathway - Lv, Jia-jia; Song, Wen-ting; Li, Xin-min; Gao, Jian-mei; Yuan, Ze-li (Frontiers in Pharmacology, 2020)
To strengthen the potency of the quinazoline core, we designed and synthesized three novel quinazoline-phenyl chlormethine conjugates (I-III) bearing a Schiff base (C=N) linker. Due to compound II effectively suppressed hepatocellular cancer (HepG2) cell growth than other two compounds in our preliminary experiment, compound II was thus selected for further anti-cancer In summary, our findings reveal that compound II, a novel synthetical phenyl chlormethinequinazoline combi-molecules, significantly induces apoptosis in liver cancer both in vivo and in vitro, at least partly, through mediating Sirt1/caspase 3 singling pathway. These findings demonstrate that compound II may be a promising potent agent against hepatocellular carcinoma.